Exploration of Conformational Spaces of High‐Mannose‐Type Oligosaccharides by an NMR‐Validated Simulation1. Issue 41 (4th September 2014) - Yamaguchi, Takumi; Sakae, Yoshitake; Zhang, Ying; Yamamoto, Sayoko; Okamoto, Yuko; Kato, Koichi
Abstract Exploration of the conformational spaces of flexible biomacromolecules is essential for quantitatively understanding the energetics of their molecular recognition processes. We employed stable isotope‐ and lanthanide‐assisted NMR approaches in conjunction with replica‐exchange molecular dynamics (REMD) simulations to obtain atomic descriptions of the conformational dynamics of high‐mannose‐type oligosaccharides, which harbor intracellular glycoprotein‐fate determinants in their triantennary structures. The experimentally validated REMD simulation provided quantitative views of the dynamic conformational ensembles of the complicated, branched oligosaccharides, and indicated significant expansion of the conformational space upon removal of a terminal mannose residue during the functional glycan‐processing pathway.